Influence of latent iron deficiency on cognitive abilities in students - Sheikh, Ali Dani; Babienko, V.; Kobolev, E. (Journal of Education, Health and Sport, 2022)
The aim of the study is to assess the impact of latent iron deficiency on students' cognitive abilities. Material and methods. The study was conducted during 2018-2021 at the Department of Hygiene and Medical Ecology of Odessa National Medical University. A survey of 188 medical students aged 18-20 was conducted using a screening survey. Estimation of the qualitative content of iron compounds in the diet was performed by a calculation method using the USDA / FDA database. Persons with probable iron deficiency were examined for hemoglobin, erythrocytes, hematocrit (general clinical blood test) and serum ferritin. Additionally, the cognitive abilities of people with latent iron deficiency were assessed using MoSA, TMT, GPB, Schulte tables and TAS-20. As a control, 30 students aged 18-20 years who showed no signs of latent or overt iron deficiency were interviewed. Statistical processing was performed by methods of variance and correlation anamnesis using the software Statistica 13.0 (TIBCO, USA). Results. When evaluating diets, probable iron deficiency was identified in 69 (36.7%) students surveyed. A significant number of students reported signs of iron deficiency, namely general weakness (27 or 14.4%), increased fatigue (30 cases or 15.9%), pale skin and mucous membranes (6 or 3.2%), drowsiness (8 or 4.3%), dry mouth (11 or 5.9%), brittle hair (4 or 2.1%), bleeding gums (3 or 1.6%). In isolated cases, hyposmia, dysgeusia and dysphagia have occurred. Probable iron deficiency was found at the previous stage of the study in 29 (15.4%) patients, they subsequently underwent verifying laboratory tests. In the analysis of the obtained data, the diagnosis of mild iron deficiency anemia was confirmed in 2 (6.9%) girls. Latent iron deficiency was identified in 16 (55.2%) students, among whom girls predominated (10 people or 62.5%). Subsequent studies have shown that a significant number of students with latent iron deficiency showed moderate signs of decreased cognition. Conclusions: 1. The frequency of latent iron deficiency in the surveyed contingent was 8.5%, with an absolute predominance of girls (62.5%). 2. Latent iron deficiency in student youth can be manifested by cognitive impairment, and therefore affect academic performance. 3. The most pronounced correlation was found for ferritin content and severity of alexithymia (r = -0.61).